Soil respiration and microbial communities across different farming management of shaded coffee and pines on agroforestry system - CAHYO PRAYOGO; NOVI ARFARITA; FITRIANA LUTHFININGSIH; NURULITA FAJRINA; NAYLIL AULA SHOLIH (Biodiversitas Journal of Biological Diversity, 2026)
Abstract. Prayogo C, Arfarita N, Luthfiningsih F, Fajrina N, Sholih NA. 2026. Soil respiration and microbial communities across different farming management of shaded coffee and pines on agroforestry system. Biodiversitas 27 (2): d270205. https://doi.org/10.13057/biodiv/d270205. Small-scale shaded coffee and pine agroforestry has been recognized to have some advantages in ecological but it is vulnerable to climate change and yields sustainability. This study aimed to examine the impact of contrasting farmer management on soil properties, microbial respiration, and microbial structure and activities. The design of the experiment was a nested Randomized Complete Block Design (RCBD) of four contrasting farming management systems (LC, MC, HC, and BAU plots), consisted of three blocks of different position of sampling (zona A: 0.5 cm from coffee, B: 0.5 cm from pine, and C: in between coffee and pine stand, treated as nested sample), was within the size of 20 x 20 m, with 3 replicates in separate blocks, resulting 36 plots in total. Variables were measured: (soil C, N, C/N ratio, MBC, total/functional bacteria, respiration, coffee and pine litter, tree population, coffee production, and litter input). Data were analyzed using ANOVA, followed by DMRT (5%), and multivariate PCA, which were employed to group the treatments based on selected variables. The results showed that the HC plot, with the highest coffee population, produced the highest canopy cover, litter input, and the lowest soil pH, but it provided the largest total bacterial population and greatest soil respiration and MBC, which was significantly different from other plots. The least pine population at BAU plots increases soil C and N, contains 2 x higher N-fixing bacteria than treatment, and produces the greatest coffee yields. PCA revealed that there was a strong relationship between soil respiration and total soil bacteria population, soil MBC, soil C/N ratio and pine litter, significantly separating the different farmer management.